Ultrasound‐Guided Placement of a Paddle Lead Onto Peripheral Nerves: Surgical Anatomy and Methodology. Issue 1 (5th September 2013) - Gofeld, Michael; Hanlon, John G.
<x xml:space="preserve">Abstract</x> Objectives Implanted peripheral nerve stimulation is one of the earliest developed methods of neuromodulation for the treatment of chronic neuropathic pain. It is traditionally performed by surgical exposure and implantation of a paddle lead. Ultrasound‐guided percutaneous placement of cylindrical leads has been proposed as an alternative. However, those leads are fragile and prone to migration. Minimally invasive paddle lead implantation may improve long‐term results while minimizing surgical insult. A feasibility laboratory study was performed. Materials and Methods Ultrasound‐guided placements of a narrow paddle lead were performed in the upper and lower extremities of a human cadaver. Ultrasonography was used to record the lead position relative to the target nerves. Dissections were performed, and digital photography was completed. Anatomic images were analyzed. Results All experiments were successfully accomplished. Although ultrasound localization of the upper extremity nerves was straightforward and clear, all procedural steps were technically easier at the lower extremity. For the latter, fewer attempts were required to maintain the lead in the desired tissue plane. Ultrasound revealed an acoustic shadowing of the underlying nerves in both the short‐ and long‐axis views by the inserted lead. All dissections revealed a parallel to the nerve lead placement with at least four contacts facing the nerve. The lead appeared to be more mechanically stable at the lower extremity. Conclusions This anatomic study confirmed technical feasibility of percutaneous placement of a narrow paddle‐type lead for the peripheral nerve stimulation that may potentially improve stimulation and reduce migrations.